IMPLEMENTATION OF CORPORATE GOVERNANCE MECHANISM IN UNHUSKED RICE AND RICE PROCUREMENT CONDUCTED BY BULOG EAST JAVA REGIONAL DIVISION - Yudiani, Triana Dewi (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research was conducted in Bulog Regional Division of East Java. This study aims to determine the company's accounting performance in BULOG procurement of unhusked rice and rice when using patterns and Implementation of Corporate Governance principles and determine the mechanism performance of companies in the Bulog division of unhusked rice and rice procurement, and when using high quality human resources management. This study uses a qualitative method. The results showed that In the aspect of transparency, Bulog gives an information of Bulog accounting in rice buying and selling on Bulog member, but it does not show the financial statements of the procurement and purchase of grain which areopenly tothe public. In the aspect of accountability, it is reported through LIS (Logistics Information System) room at that the analysis of the Bulog accounting integrated with the Bulog centre in the internal audit assignment. Responsibilities Aspect in Bulog Regional Division of East Java Bulog area is responsibility accounting based on SAB (Bulog Accounting Standards) in accordance with the basic principles of national financial accounting. The fairness aspect is based on the protection of worker equitably based on SOP (Standard Operating Procedure). Explanation SOP from the decision of the company director in .Article 293 that every head of the organization shall over see the implementation of subordinate task and if it irregularities, it will be subject to the laws and regulations without distinguishing the perpetrator.Keywords:Company’s Accounting, Implementation of Corporate Governance.